The Effect of Welding Current and Welding Speed on Hardness and Structure of Lap Joint Between SS400 Steel and SUS304 Stainless Steel in Robotic Gas Metal Arc Welding Process - Taptimdee, Weerapol; Thammachot, Narongsak; Suwittayaruk, Peeradaech; Chanchana, Atthakorn; Mayai, Amornsak (Journal of Advanced Development in Engineering and Science, 2026)
The objective of this research was to investigate the influence of welding current and welding speed on the hardness, macrostructure, and microstructure of lap joints between SUS304 stainless steel and SS400 carbon steel. Using a robotic Gas Metal Arc Welding process in a vertical-down position, the research utilized an ER309L filler wire with 100% argon shielding gas. Welding parameters included three current levels (120, 140, and 160 A) and three welding speeds (200, 250, and 300 mm/min). The results indicated that increasing the welding current increased the weld bead's width, height, and penetration. Conversely, these properties decreased with an increase in welding speed. A maximum weld bead hardness was achieved at a current of 140 A and a speed of 250 mm/min. Macro and microstructural analysis showed no surface discontinuities. The changes in welding current and speed influenced the microstructure, which correlated with the hardness results.